2016
DOI: 10.1056/nejmoa1509981
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib (ACP-196) in Relapsed Chronic Lymphocytic Leukemia

Abstract: Background Irreversible inhibition of Bruton tyrosine kinase (Btk) by ibrutinib represents a significant therapeutic advance for chronic lymphocytic leukemia (CLL). However, ibrutinib also irreversibly inhibits alternative kinase targets, which potentially compromise its therapeutic index. Acalabrutinib (ACP-196) is a more selective irreversible Btk inhibitor specifically designed to improve upon the safety and efficacy of first generation Btk inhibitors. Methods Sixty-one patients with relapsed CLL were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
731
2
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 803 publications
(794 citation statements)
references
References 34 publications
26
731
2
17
Order By: Relevance
“…Finally acalabrutinib has little toxicity on platelets which is an off-target effect of ibrutinib potentially leading to platelet dysfunction and bleeding. 1 It should be noted that we did not investigate in detail the direct effects of acalabrutinib on CLL cells, including apoptosis induction, alone and in combination with anti-CD20 monoclonal antibodes. This should be done in future work, using samples from a large panel of CLL patients sensitive or resistant to ibrutinib.…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally acalabrutinib has little toxicity on platelets which is an off-target effect of ibrutinib potentially leading to platelet dysfunction and bleeding. 1 It should be noted that we did not investigate in detail the direct effects of acalabrutinib on CLL cells, including apoptosis induction, alone and in combination with anti-CD20 monoclonal antibodes. This should be done in future work, using samples from a large panel of CLL patients sensitive or resistant to ibrutinib.…”
Section: A B Cmentioning
confidence: 99%
“…12 Acalabrutinib monotherapy has shown promising activity in animal models of CLL and lymphoma 13,14 and in CLL patients. 1,15 Like ibrutinib, acalabrutinib is already being tested in combination with anti-CD20 monoclonal antibodies, in particular in B-cell non-Hodgkin lymphoma (www.clinicaltrials.com). The data presented here suggest that acalabrutinib may be usefully combined with these antibodies.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its clinical activity (in particular, durability of response) was inferior to that of ibrutinib or acalabrutinib. 3,13 Although the reasons are not completely clear, given reasonably high BTK occupancy in most patients on BID dosing, it seems likely that highly variable PK and PD limited the ability of CC-292 to consistently reach its target in vivo. As the importance of BCR signaling is now well established in the treatment of CLL, the suboptimal efficacy of CC-292 represents a valuable cautionary clinical experience in the development of next generation BTK inhibitors.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Most common side effects were headache, diarrhea, and weight gain and there were no cases of atrial fibrillation have been reported to date. 36 Ongoing phase III trials include acalabrutinib in isolation or combination in the first-line (NCT02475681) and in R/R CLL (NCT02029443; NCT02477696).…”
Section: Bruton Tyrosine Kinase Inhibitorsmentioning
confidence: 99%